1998
DOI: 10.1007/s004670050491
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of microalbuminuria in children with sickle cell disease

Abstract: Renal involvement is common in homozygous sickle cell disease (HbSS), including glomerular hypertension and hypertrophy similar to that seen in rodent models of ablative nephrectomy and stage I diabetic nephropathy (DN). The proteinuria in the rodent models is attenuated by angiotensin converting enzyme inhibition (ACEI). Microalbuminuria (MA) is a sensitive marker for renal involvement in DN prior to the development of proteinuria, and is also attenuated with ACEI. Elevated urinary microalbumin/creatinine rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
79
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(104 citation statements)
references
References 21 publications
19
79
6
Order By: Relevance
“…Therefore, it is not known whether patients with microalbuminuria will progress to macroalbuminuria. However, indirect evidence in children suggests that microalbuminuria could precede the development of macroalbuminuria in adults (14,15). In children, the development of microalbuminuria follows an age-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is not known whether patients with microalbuminuria will progress to macroalbuminuria. However, indirect evidence in children suggests that microalbuminuria could precede the development of macroalbuminuria in adults (14,15). In children, the development of microalbuminuria follows an age-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…In children, the development of microalbuminuria follows an age-dependent manner. For instance, Dhranidharka et al (14) reported that microalbuminuria was not present in children who were younger than 7 yr but reached 43% in the second decade of life. In a similar study by Wigfall et al (15), the authors found an age-dependent occurrence of dipstick proteinuria: Proteinuria was not present in children who were 0 to 6 yr of age, but it occurred in 7% of children who were aged 7 to 10 yr and in 10% of children who were aged 13 to 17 yr.…”
Section: Discussionmentioning
confidence: 99%
“…In a cross-sectional study of 410 patients with SCD aged 2-21 (mean age 11) years, 23% had the HbSS form of SCD, with elevated urinary albumin excretion (≥30 mg/g), while other investigators have reported a HbSS prevalence of 16-27% in the childhood SCD population [18,20,21]. Further progressive kidney injury and CKD is reflected in a declining and abnormally low GFR.…”
Section: Sickle Cell Nephropathy In Childrenmentioning
confidence: 99%
“…Thus, the early recognition of SCAN at the time of chronic kidney disease (CKD) stage I (4) and the focus on the early steps of the natural history of this nephropathy, together with the recognition of the associated clinical and biologic risk factors are of major interest. Previous works have reported the occurrence of SCAN very early in childhood, as soon as 7 years of age (5), with a prevalence of microalbuminuria of 26.5% increasing up to 40% in young adults. Macroalbuminuria is reported in 26% to 40% of patients with sickle cell anemia (SCA) depending on the age and may lead to nephrotic syndrome (1), revealing a focal glomerulosclerosis.…”
mentioning
confidence: 98%